Carbonic Anhydrase in Pacific Abalone Haliotis discus hannai: Characterization, Expression, and Role in Biomineralization - Sharker, Md. Rajib; Kim, Soo Cheol; Hossen, Shaharior; Sumi, Kanij Rukshana; Choi, Sang Ki; Choi, Kap Seong; Kho, Kang Hee (Frontiers in Molecular Biosciences, 2021)
Carbonic anhydrases (CAs) are universal zinc ion containing metalloenzymes that play a pivotal role in various physiological processes. In this study, a CA I (designated as Hdh CA I) was isolated and characterized from the mantle tissue of Pacific abalone, Haliotis discus hannai. The full-length cDNA sequence of Hdh CA I was 1417-bp in length, encoding a protein of 337 amino acids with molecular weight of 37.58 kDa. Hdh CA I sequence possessed a putative signal peptide of 22 amino acids and a CA catalytic function domain. The predicted protein shared 94% and 78% sequence identities with H. gigantea and H. tuberculata CA I, respectively. Results of phylogenetic analysis indicated that Hdh CA I was evolutionarily close to CA I of H. gigantea and H. tuberculata with high bootstrap values. Significantly higher levels of Hdh CA I mRNA transcript were found in mantle than other examined tissues. In situ hybridization results showed strong hybridization signals in epithelial cells of the dorsal mantle pallial, an area known to synthesize and secrete proteins responsible for the nacreous layer formation of shell. This is the first study on Hdh CA I in H. discus hannai and the results may contribute to further study its physiological functions in shell biomineralization of abalone.